2021
DOI: 10.1093/nar/gkab888
|View full text |Cite|
|
Sign up to set email alerts
|

Binding of DNA origami to lipids: maximizing yield and switching via strand displacement

Abstract: Liposomes are widely used as synthetic analogues of cell membranes and for drug delivery. Lipid-binding DNA nanostructures can modify the shape, porosity and reactivity of liposomes, mediated by cholesterol modifications. DNA nanostructures can also be designed to switch conformations by DNA strand displacement. However, the optimal conditions to facilitate stable, high-yield DNA–lipid binding while allowing controlled switching by strand displacement are not known. Here, we characterized the effect of cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 85 publications
2
24
0
Order By: Relevance
“…For the proximal spacer design, a high yield was observed for all configurations, with yields in the range of 90-95% for the circular configurations and 95-101% for the rectangular configurations (Figure 2B(i)), suggesting minimal aggregation. This was expected based on previous studies, which show low aggregation for proximal placement [14] but also lower membrane-binding yield [37]. Note that a yield of over 100% is possible as these yields are normalized to the control lane, and gel loading and analysis error can be up to 10% RSD [47].…”
Section: Spacersupporting
confidence: 74%
See 3 more Smart Citations
“…For the proximal spacer design, a high yield was observed for all configurations, with yields in the range of 90-95% for the circular configurations and 95-101% for the rectangular configurations (Figure 2B(i)), suggesting minimal aggregation. This was expected based on previous studies, which show low aggregation for proximal placement [14] but also lower membrane-binding yield [37]. Note that a yield of over 100% is possible as these yields are normalized to the control lane, and gel loading and analysis error can be up to 10% RSD [47].…”
Section: Spacersupporting
confidence: 74%
“…The DOT is a flexible single-layered 24-helix rectangular 2D DNA nanostructure (60 × 90 nm), while the DOB is a barrel-shaped rigid 3D structure (52 × 30 nm). In a previous study, we showed that increasing the number of cholesterols does not always increase the membrane binding, and that the optimum number of cholesterols for the DOT structure is 4-8 [37]. Here, we compare the aggregation for two different configurations of cholesterols on the DOT: a fourcholesterol rectangular (R) configuration and a six-cholesterol circular (C) configuration.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Importantly, it was reported that aggregation lowers the membrane insertion rate of DNA structures [20,47], and our observations showed similar effects even for shielded structures and in the presence of oPOE surfactants. Thus, various methods have been employed to minimize the impact of clustering [33]: optimizing the separation between cholesterols and decreasing the length of a spacer, folding in the presence of the surfactant [27,31,33], adding cholesterol in the second folding step [24,25,33], and, finally, the shielding technique used in this work [22,33,48,49].…”
Section: Discussionmentioning
confidence: 99%